2012
DOI: 10.1002/chp.21131
|View full text |Cite
|
Sign up to set email alerts
|

Communication Skills Training Increases Self-Efficacy of Health Care Professionals

Abstract: Although the study was conducted in a real-world setting with many competing demands, a communication course produced an increase in self-efficacy. This result was observed for doctors, nurses, nursing assistants, and medical secretaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 20 publications
9
91
0
4
Order By: Relevance
“…This gave us the opportunity to study whether a positive effect could be found when the intervention was implemented in an entire organization. Previously, we have shown that the staff increased their self-efficacy both in relation to the communication with patients and with colleagues after having participated in the communication training course [15] . The question was then whether this increase would persist.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This gave us the opportunity to study whether a positive effect could be found when the intervention was implemented in an entire organization. Previously, we have shown that the staff increased their self-efficacy both in relation to the communication with patients and with colleagues after having participated in the communication training course [15] . The question was then whether this increase would persist.…”
Section: Discussionmentioning
confidence: 93%
“…This questionnaire was further adapted for the present study and expanded with questions about inter-collegial communication [15] . The questionnaire was structured with eight questions elucidating the health care professionals' perceived self-efficacy in communication with patients and eleven questions concerning communication with colleagues.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caring words, listening with all attentions, using a calm tone of voice, softly looking in the eyes, a smile and a genuine concern for well-being of the communicate are all what are needed and attainment of such mental state can be triggered automatically when one thinks about positive and loving thoughts. However, only the golden touch of love for all fellow human beings is most a needed [41][42][43][44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…Other reports have explored self-efficacy and patient care outcomes [Dahl & Hall, 2013;Jungert & Rosander, 2010]. Previous research reported ways to increase self-efficacy among healthcare professionals through communication training [Norgaard, Ammentorp, Kyvik & Kofoed, 2012] and problem-based learning [Darkwah, Ross, Williams, & Madill, 2011;Jungert & Rosander, 2010].…”
Section: Introductionmentioning
confidence: 99%